Monetary policy and bank risk-taking: Evidence from the corporate loan market - Paligorova, Teodora; Santos, João A.C. (Journal of Financial Intermediation, 2017)
Our study of the corporate loan pricing policies of U.S. banks over the past two decades shows that loan spreads for riskier firms become relatively lower during periods of monetary policy easing compared to tightening. This effect is driven by banks with greater risk appetite, measured from individual banks’ answers to the Senior Loan Officers Opinion Survey. Our results hold with different fixed effects that account for time-varying observed and unobserved heterogeneity of credit demand and bank lending conditions that are not directly related to monetary policy. Together with our survey-based measure of bank risk appetite, we provide compelling evidence of the presence of a bank risk-taking channel of monetary policy in the U.S.